(untitled) (Acta Scientiarum. Health Sciences, 2021)
The aim of this study was to detect early hypertension, diabetes and obesity, as well as their risk factors, in 105 young shooters from Tiro de Guerra 11-002 in the city of Ituiutaba-MG. This is a cross-sectional mixed study. A semi-structured questionnaire that contained questions related to the sociodemographic context, health status, lifestyle, eating habits, and psychosocial variables was applied. Blood pressure, anthropometric indexes, and lipid and glycemic profiles were measured. Descriptive and inferential statistics, including Pearson’s correlation test and Spearman’s coefficient, considering significative value (p < 0.05). The shooters had an average of 18.9 years old, most educated and brown. Anthropometric indices indicated a mainly eutrophic population, and normotensive and desirable lipid and glycemic profiles. However, overweight, high blood pressure, and self-declaration of family history for chronic diseases were identified. In addition, most shooters affirmed to ingest alcoholics beverages, to have insufficient time of physical activity, and to be aware of their levels of stress, pressure and anxiety and a few hours of sleep. Overall, the shooters showed good anthropometric and biochemical indicators of blood. Risk behavior, such as drinking alcoholic beverages and smoking, low level of physical activity and self-perception of stress, anxiety and pressure were also noted.